Aquatic ecotoxicity of lanthanum : a review and an attempt to derive water and sediment quality criteria - Henning Herrmann and Jürgen Nolde and Svend Berger and Susanne Heise (Ecotoxicology and environmental safety, 2016)
Rare earth elements (REE) used to be taken as tracers of geological origin for fluvial transport. Nowadays their increased applications in innovative environmental-friendly technology (e.g. in catalysts, superconductors, lasers, batteries) and medical applications (e.g. MRI contrast agent) lead to man-made, elevated levels in the environment. So far, no regulatory thresholds for REE concentrations and emissions to the environment have been set because information on risks from REE is scarce. However, evidence gathers that REE have to be acknowledged as new, emerging contaminants with manifold ways of entry into the environment, e.g. through waste water from hospitals or through industrial effluents. This paper reviews existing information on bioaccumulation and ecotoxicity of lanthanum in the aquatic environment. Lanthanum is of specific interest as one of the major lanthanides in industrial effluents. This review focuses on the freshwater and the marine environment, and tackles the water column and sediments. From these data, methods to derive quality criteria for sediment and water are discussed and preliminary suggestions are made.
Keywords: Ecotoxicity; Lanthanum; Rare earth elements; Review; Sediment quality criteria; Water quality criteria